Twenty Years Medical Informatics Education at Heidelberg/Heilbronn: Evolution of a Specialized Curriculum for Medical Informatics - Haux, R.; Leven, F. J. (Methods of Information in Medicine, 1994)
The medical informatics curriculum at University of Heidelberg/School of Technology Heilbronn started in 1972 as a specialized university curriculum. In this paper, we report on 20 years of experience and the evolution of this educational approach with respect to structure and content of the curriculum. We emphasize that this evolution parallels the development of medical informatics to a medical discipline in its own right, with distinct application domains and specific methodological approaches. Based on our experience and on recommendations from the national and international community, we describe and discuss the features of the curriculum.
Keywords: Medical Informatics; Education; Training